Respuesta :
Answer:
Simplifying
2(x + 3) + 3x + -10 = 0
Reorder the terms:
2(3 + x) + 3x + -10 = 0
(3 * 2 + x * 2) + 3x + -10 = 0
(6 + 2x) + 3x + -10 = 0
Reorder the terms:
6 + -10 + 2x + 3x = 0
Combine like terms: 6 + -10 = -4
-4 + 2x + 3x = 0
Combine like terms: 2x + 3x = 5x
-4 + 5x = 0
Solving
-4 + 5x = 0
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '4' to each side of the equation.
-4 + 4 + 5x = 0 + 4
Combine like terms: -4 + 4 = 0
0 + 5x = 0 + 4
5x = 0 + 4
Combine like terms: 0 + 4 = 4
5x = 4
Divide each side by '5'.
x = 0.8
Simplifying
x = 0.8
Step-by-step explanation:
Remove the pharentheses
2x+6+3x-10
Collect like terms
5x+6-10
Calculate
=5x-4
2x+6+3x-10
Collect like terms
5x+6-10
Calculate
=5x-4